DANA BOS DAN KUALITAS PENDIDIKAN - Pertiwi, Sri Indah (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2023)
This study aims to determine the effectiveness of BOS funds as measured by several educational indicators, including average years of schooling (RLS), school life expectancy (HLS), net enrollment rate (APM), gross enrollment ratio (APK), and number of school dropouts. Type and source of data used is secondary data. Data collection technique through literature studies with data analysis methods, namely descriptive qualitative analysis. The research results show that the impact of BOS funds on the quality of education is still not effective. In 2010-2021, RLS and HLS in Indonesia have continued to increase but not significantly for the last 12 years. The APM and APK for 2017-2021 also show inequality between each level of education where community participation is low in studying at the junior and senior high school levels. This has an impact on the high number of dropouts, especially at the elementary level. Thus, BOS funds can be more focused on reducing the dropout rate by supervising the implementation of the BOS program so that the use of BOS funds can be more effective.